Bioinspired Discovery of Chemical Reactions and Biological Probes - Griffiths, Brendan M.; Burl, Jessica D.; Wang, Xiang (Synlett, 2016)
Indole alkaloids are a large and diverse family of natural products that display a variety of medicinal properties. These natural products have consistently proven difficult to synthesize, due in large part to their complex skeletons and sterically hindered quaternary carbon centers. We have reported the efficient syntheses of polycyclic indole derivatives using gold catalysts, which selectively activate alkynylindoles for tandem cyclizations with high stereospecificity. The facile nature of these methods has allowed previously implausible diversity syntheses to be carried out yielding a large and highly diverse library of polycyclic indolines. Biological screenings revealed compounds that selectively re-sensitize methicillin-resistant Staphylococcus aureus (MRSA) to β-lactam antibiotics, which may herald a new way of staving off the incursion of drug-resistant strains of common human pathogens.1 Introduction2 Gold-Catalyzed Cyclizations3 Chemical Probe Discovery4 Outlook
Keywords: indole alkaloid; gold catalysis; antibiotic resistance; resistance-modifying agent; MRSA